Financial Management Policy of Transfer to Regional and Village Funds, Regional Budget, and Special Autonomy - Adolf Z. D. Siahay (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Fiscal decentralization highlights the importance of central government transfers, which aim to reduce income disparities and promote regional development. The effectiveness of these transfers depends on the ability of local governments to manage and allocate funds according to the needs of the community. The purpose of this study is to analyze and highlight several articles published on financial management policies for transfers to regions and villages, regional revenue and expenditure budgets, and special autonomy. The methods used include a literature review to determine how well financial management policies work and their impact on fiscal autonomy, by looking at regions with and without special autonomy. Selected articles published in the last 10 years (2019-2024) were used to ensure relevance to the current policy context. All these results highlight the importance of financial management policies in supporting regional autonomy and growth, particularly through good governance and effective resource allocation. This study concludes that the efficient implementation of policies is key to ensuring that local governments can manage allocated finances and align them with regional development objectives. This is important for promoting local autonomy and achieving sustainable economic growth. These impacts highlight the importance of financial management policies in determining local autonomy and growth, emphasizing the need for well-planned policy formulation and implementation.